Estudo de nanopartículas para preparação de compósitos com acoplamento magnetoelétrico - Clabel Huamán, José Luis (2009)
In recent years the necessity of new devices, in the electroelectronic industry, has lead to an increasing interest in materials called magnetoelectric (ME) or multiferroic (MF). Multiferroic is the term used to classify the materials that exhibit magnetic and electric orders simultaneously. In this sense, the idea of producing materials and smart devices have attracted the attention of many researchers from different fields of knowledge. From the technological point of view, the simultaneous mutual control of electrical and magnetic properties generates new possibilities of applications. However the number of candidate for these applications materials is limited and the effects are typically very small and in some cases observed in the low temperature. Therefore, the search for room temperature multiferroic materials is very import for technological application of these materials as well as from the academic stand point. This work aimed the preparation of new multiferroic materials suitable for technological application. We performed a systematic study on the preparation of composites. Both compounds were synthesized using Pechini method, further, they were characterized by dilatometry, densification, X-ray diffraction, electronic microscopy, magnetization and resistivity measurements. We found the best results for the manganite prepared from solution with pH=0 and then calcinated at 900 for 6 hours. After that, the powder were sinterized at 1000 for 2 hours. For bfor 2 hours.